Creating shared reality in interpersonal and intergroup communication: the role of epistemic processes and their interplay. (1st January 2017) - Echterhoff, Gerald; Higgins, E. Tory
ABSTRACT: We describe research on the creation of shared reality in communication, emphasizing the epistemic processes that allow communicators to achieve confident judgements and evaluations about a communication topic. We distinguish three epistemic inputs: (1) the communicator's own judgement about the topic (judgement of communicator); (2) the communicator's perception of the audience's judgement about the topic (judgement of audience); and (3) the communicator's message to the audience about the topic (message of communicator). We argue that the influence of each input increases with the communicator's confidence in the validity of that input. We review a variety of empirical studies in terms of this framework. We also address barriers to shared-reality creation in intergroup communication and describe interventions that work by increasing the validity strength of judgement of an outgroup audience. We discuss the relation between the present research and other approaches to social influence and social sharing.